Evolution of Solid Products Formed During the Cathodic Decomposition of Chalcopyrite at Different Energetic Conditions in Acetic Acid - Laura Denisse Jasso-Recio; Juan Carlos Fuentes-Aceituno; Roberto Pérez-Garibay; Aldo Valentín Enríquez-Farías; Alfredo Flores-Valdés; Jesús Torres-Torres (Metals)
This paper presents a systematic analysis of the solid products formed during the cathodic decomposition of chalcopyrite using the acetic acid system. The reduction of chalcopyrite was assessed using different electrochemical and surface characterization techniques. The effect of multiple cathodic polarizations of chalcopyrite immersed in acetic acid was evaluated on the formation of less refractory copper species through the interaction of chalcopyrite with monoatomic hydrogen. The reduction products obtained were characterized by the FESEM/EDS techniques. The results revealed that the iron content in the chalcopyrite lattice was continuously decreased and released into the acetic acid solution when the polarization cycles were increased from 1 to 11 starting from OCP to −2.2 V vs. SHE. The chemical analyses revealed that iron released into the solution corresponds to 0.085 and 1.95 mg/L for 1 and 11 cycles, respectively. The open circuit potential (OCP) measurements of the solid products were shifted to more cathodic potentials than that of chalcopyrite, confirming the possibility to form less refractory species in this weak organic acid. Finally, the FESEM-EDS and XRD analyses showed that chalcopyrite refractoriness decreased, producing Cu, Cu2S, CuS, CuO, and C4H6CuO4H2O species depending on the applied energetic condition.